Studien zur Geschichte kapitalistischer Organisationsformen. Jakob Strieder (Journal of Political Economy, 1915)
This study of early capitalistic organizations has revealed much interesting information relative to the character and extent of these industrial forms in the Middle Ages.The Montan industry furnishes the illustration of the earli- est capitalistic organization.In the mediaeval period there existed Kartels and